Surface engineering of nanoporous silicon photocathodes for enhanced photoelectrochemical hydrogen production. Issue 18 (9th August 2022) - Jian, Jing-Xin; Yao, Ming-Ming; Liao, Jia-Xin; Zhou, Mu-Han; Chen, Yi-Jing; Deng, Meng-Xin; Huang, Yu-Mei; Liu, Chao-Ping; Tong, Qing-Xiao
Abstract : Comparison of the nanostructured Si photocathodes fabricated by chemical etching (c-Si), electrochemical etching (ec-Si) and photoelectrochemical etching (pec-Si) and their dramatically enhanced PEC water splitting. Abstract : Silicon (Si) is a promising semiconductor material in photoelectrochemical (PEC) H2 evolution due to its advantages of being an earth-abundant element, non-toxicity, broad absorption of the solar spectrum, high saturation current and industrial fabrication. However, shortcomings such as strong sunlight reflection, low photocurrent onset potential, slow charge-transfer dynamics at the silicon/electrolyte interface, and low stability in electrolyte limit its PEC applications. In this work, surface-engineered nanoporous Si photocathodes with controllable surface morphologies were fabricated. Compared with flat Si (f-Si), chemically-etched Si (c-Si) and electrochemically-etched Si (ec-Si), PEC-etched Si (pec-Si) exhibits advantages such as high light-harvesting efficiency, a large surface area and improved electron-transfer, resulting in dramatically enhanced PEC water splitting. Additionally, n-type TiO2 is deposited on the Si surface to prepare a p–n heterojunction and a protective layer, which further increases the charge separation and water splitting stability. Under AM1.5G illumination, the optimized pec-Si/TiO2 photocathode gives a high photocurrent density of −15.53 mA cm −2 at 0 VRHE, a large onset potential of 0.60 VRHE, and a high applied bias photon-to-current efficiency of 2.22% for H2 production. The surface engineering of the nanoporous structures and p–n heterojunction brings insights into the construction of efficient photoelectrodes for solar conversion.